2003
DOI: 10.1111/j.1745-4565.2003.tb00363.x
|View full text |Cite
|
Sign up to set email alerts
|

BACTERIOCIN EXPOSURE AND FOOD INGREDIENTS INFLUENCE ON GROWTH AND VIRULENCE OF LISTERIA MONOCYTOGENES IN A MODEL MEAT GRAVY SYSTEM

Abstract: The antilisterial activity of bacteriocin-producing Lactobacillus sakei 1 bac+ alone and combined with food ingredients (sodium chloride, D-glucose, oregano, black pepper) was studied in a model meat gravy (1.8% proteose peptone, 1.2% meat extract, 0.6% yeast extract, 2.0% corn starch) kept under refiigeration for 10 days. Two strains of L. monocytogenes (serovpes 4b and 1/2a) were employed in coinoculation experiments and Lactobacillus sakei ATCC 15521 was used as a negative control for bacteriocin producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
2
9
1
Order By: Relevance
“…According to Kathariou (2002), stresses caused by refrigeration, dehydration, freezing, heating, acids and salts, as well the exposure to disinfectants and other antimicrobial substances are of special relevance for the physiological status and virulence of this pathogen in foods. In fact, food composition seems to have an effect on LLO production by L. monocytogenes (Alves et al, 2003;Kim et al, 1994), although we have demonstrated in this report that L. sakei 1 bacteriocin alone did not modify the secretion of this virulence factor.…”
contrasting
confidence: 67%
See 2 more Smart Citations
“…According to Kathariou (2002), stresses caused by refrigeration, dehydration, freezing, heating, acids and salts, as well the exposure to disinfectants and other antimicrobial substances are of special relevance for the physiological status and virulence of this pathogen in foods. In fact, food composition seems to have an effect on LLO production by L. monocytogenes (Alves et al, 2003;Kim et al, 1994), although we have demonstrated in this report that L. sakei 1 bacteriocin alone did not modify the secretion of this virulence factor.…”
contrasting
confidence: 67%
“…These could be other important factors that influenced L. monocytogenes haemolytic activity in the work done by Alves et al (2003).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Results presented in this study are in agreement with those previously reported (Alves et al . ), demonstrating that counts of LAB were not altered in the presence of pathogenic bacteria. Roller et al .…”
Section: Resultsmentioning
confidence: 90%
“…Bacteriocinogenic L. sakei 1 was tested in a model food system by Alves et al. (2003) and it was more effective to inhibit L. monocytogenes than a nonbacteriocinogenic strain of the same species.…”
Section: Introductionmentioning
confidence: 99%